Creating Cool MINDSTORMS NXT Robots - Benedettelli, Daniele. (Apress : Imprint: Apress, 2008)
Build and program MINDSTORM NXT robots with Daniele Benedettelli, one of the world's most respected NXT robot builders. He shows you how to build and program them from scratch, starting with the simplest robots and progressing in difficulty to a total of seven award–winning robots! You can download all the code, along with low–resolution videos that show how your robot works when it's finished. You don't need to be a programmer to develop these cool robots, because all the code is provided, but advanced developers will enjoy seeing the secrets of Benedettelli's code and techniques revealed.